BIO-METHANE POTENTIAL METHOD DEVELOPMENT AND PROCESS OPTIMIZATION OF A DRY BIODIGESTER - Hernandez, Jorge A (My University, 2015)
Fossil fuels have been a crucial energy source for years. Their use come at a high cost with detrimental effects to the environment, including climate change, which affects both fauna and flora worldwide. Biogas production is a safe process by which products such as food and yard waste and feces are used as substrates for methane production. This serves as an alternative method to transform methane, a greenhouse gas, into electricity, thus benefiting both environment and population. The German Institute of Standardization or Deutsches Institut fur Normung (DIN) has developed a method for the analysis of biogas production. This method uses eudiometers, a laboratory glass device that measure changes in gas volume, to measure quantity and quality of biogas. The Automatic Methane Potential Test System (AMPTS) is a newly developed method, which makes use of an automated system to measure biogas production. The study looks at the AMPTS as a valid method for biomethane potential analysis (BMP)s, comparable to the DIN method. These methods were compared for analyzing biogas production with identical substrates over the course of 3-6 weeks. The substrates included, were microcrystalline cellulose, Smucker's jelly, lactose pellets, potato sludge, paper sludge, cyanobacterial biomass, parlor water, manure scrape, used bedding and fresh straw. Biogas production was quantified for both DIN and AMPTS. Statistical analysis showed that biogas produced using the DIN method was statistically similar to the AMPTS method (p > 0.05). This is important because it supports the hypothesis that the AMPTS method is valid for BMP analysis, which significantly decreases costs and increase efficiency, while reducing testing time to half. It also decreases the amount of methane produced from decomposing waste, by allowing rapid testing of feedstock.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science Microbiology
Keywords: Compost plants; Anaerobic treatment; Sewage - Purification; Biodegradation; Refuse and refuse disposal; Renewable energy resources